An Analysis of English-Speaking Problem in Junior High School Students at Ban Yaning School Narathiwat Thailand - Annisa Fitri Andani; Rosmita Ambarita; Happy Sri Rezeki Purba; Aisyah Nurmi; Salma Awae (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research aims to identify the most common factors of English-speaking problems faced by junior high school students at Ban Yaning School, Narathiwat, Thailand. These speaking problems identified five factors: 1) anxiety S confidence; 2) vocabulary; 3) grammar S pronunciation; 4) classroom environment S material; 5) motivation S learning strategies. This research used a quantitative descriptive approach involving 42 junior high school students as research subjects. The instruments used included a questionnaire with 5 to 6 for each statement for five main factors that the students must completed by choosing a scale 1 to 5, where 1 means ‘strongly disagree’ to 5 ‘strongly agree’, and an interview with the teacher. The result showed that students agree they have faced these factors of speaking problems including 57% from anxiety S confidence, 60% from vocabulary, 63% from grammar S pronunciation, 60% from classroom environment S material, 61% from motivation S learning strategies. These finding confirms that most of the students faced these problems and data show a declining trend in how these issues are perceived as students advance through their grades.